Dead until Dark - Harris, Charlaine (New York : Ace Books, 2008)
Love blossoms between Sookie Stackhouse, a cocktail waitress in rural Louisiana who keeps to herself because of her ability to read minds, and Bill, a tall, dark, and handsome vampire with ties to a creepy crowd that may be responsible for the death of one of Sookie's coworkers.